Epistemological Construction of Academic Self-Efficacy in Muslim Students: A Transcendental Phenomenological Study - Qudsi Mutiara Romadhon (Universitas Muhammadiyah Yogyakarta, 2025)
This Study examines the epistemological construction of academic self-efficacy in Muslim students through a transcendental phenomenological approach. This Study is motivated by the complexity of the challenges faced by Muslim students in constructing academic self-efficacy in the contemporary era, where they must balance Islamic values ​​with modern academic demands. This Study analyzes relevant literature on academic self-efficacy and Islamic epistemology in higher education using a library research method. The results show that the epistemological construction of academic self-efficacy in Muslim students has unique characteristics that integrate spiritual dimensions with academics, reflected in the concept of tawakkal in academic efforts and learning motivation as worship. These findings have implications for the importance of developing an educational approach that accommodates the integration of Islamic spiritual values ​​in the formation of Muslim students' academic self-efficacy, as well as the need for a support system that considers the uniqueness of this epistemological construction in the development of academic programs in higher education.